Evaluation of Microbial Contamination Rates in Umbilical Cord Blood Collection and Processing for Biobanking in Vietnam - Thao, Chu Thi; Tinh, Nguyen Van; Luc, Le Cong; Ha, Luong Thi Thanh; Phuc, Tran Van; Anh, Ngo Tien (VNU Journal of Science: Natural Sciences and Technology, 2021)
The umbilical cord blood (CB) has recently been considered an abundant source of hematopoietic stem cells (HSCs) for transplantation compared to bone marrow. However, the collection and processing of CB have a high risk of microbial contamination. Hence, the procedures to collect and process the UCB are carefully considered. This study evaluates the microbial contamination rate to find the frequency and distribution of bacterial organisms among CB sampling and processing in Vietnam. In addition, this study correlates with contamination rates between the delivery method, cesarean section, and vaginal delivery. The results create best practices to avoid a high level of contamination of UCB during collection and processing for biobanking.